Effects of sodium humate and probiotics on growth performance enzyme activity and microbial environment of Litopenaeus vannamei in high-density zero‐water exchange systems - Liao, Wuquan; Lin, Zexu; Liao, Minze; Xue, Yuan; Zhou, Jianing; Wang, Yue; Hou, Danqing; Sun, Chengbo (Frontiers in Marine Science, 2022)
The study investigates the outcomes of adding sodium humate and sodium humate with probiotics (Lysinibacillus, Bacillus subtilis) to culture water on the growth performance, enzyme activity, and microbial environment of shrimp. The sodium humate and probiotics concentrations were 3 mg/L and 105 CFU/mL in the culture water. Litopenaeus vannamei (0.31 ± 0.03 g) at a density of 300 shrimps/m3 were cultured in nine buckets for a 43-days culture experiment. The results showed that the survival rate (SR) of L. vannamei in sodium humate group and sodium humate with probiotics group were (88.44%) and (86.07%), with the sodium humate group outcome being significantly better than the control group. The shrimps’ final body weight and specific growth rate (SGR) in the two experimental groups were significantly higher than the control group. The feed conversion rate (FCR) was significantly lower than the control group. The ammonia nitrogen concentration in sodium humate with probiotics group was significantly lower than the control group on the 15th day. The activities of intestinal amylase, lipase, trypsin and hepatopancreas superoxide dismutase (SOD), phenol oxidase (PO), and catalase (CAT) in sodium humate group were significantly higher than the control group. Notably, SOD, PO, and lipase activities in sodium humate with probiotics group were significantly higher than the control group. Illumina MiSeq high-throughput sequencing showed that the Chao and Ace indices of the culture water microflora in experimental groups were higher than the control group, and the sodium humate group was significantly higher than the control group. At the phylum level, Proteobacteria, Bacteroidetes, and Actinobacteria were the dominant bacterial communities in the intestine and culture water of L. vannamei, Proteobacteria was the most abundant phyla. At the genus level, the relative abundance of Pseudohongiella of water microflora in the control group was significantly lower than the experimental groups. Ruggiella (15.22-19.56%) was the most abundant genera of intestinal microflora. These results infer that the addition of sodium humate enhances the growth performance, digestive enzymes, and some immune enzyme activities, improving the richness of the water microbial community of L. vannamei.